2010
DOI: 10.1021/ja102817a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Reactions, and Electronic Properties of 16 π-Electron Octaisobutyltetraphenylporphyrin

Abstract: The reaction of the doubly oxidized beta-octaisobutyl-meso-tetraphenylporphyrin (OiBTPP, 4), which has a 16 pi-electronic structure at the porphyrin core, with a variety of metal reagents was investigated. The reaction of 4 with SnCl(2) followed by ethanolysis afforded an 18 pi-electron tin complex, (OiBTPP)Sn(OEt)(2) (5), in a redox manner. No reactions were observed using zerovalent metals (Zn, Cu, and Pd). However, the reaction of 16pi [(OiBTPP)Li](+)[BF(4)](-) (6), which was easily derived from 4, with Zn,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 37 publications
4
25
0
Order By: Relevance
“…3b). This similarity between the electrooxidized porphyrin and its protonated product is not specific to the investigated porphyrins [32,33] nor is it specific to the PhCN or CH 2 Cl 2 solvent. The same ''side reaction'' involving conversion of the electrooxidized species to a protonated porphyrin with an unoxidized macrocycle also occurs in CHCl 3 but in this solvent only one major oxidation is observed for 1, 2 and 6.…”
Section: Protonation Of the Phosphorylated Free-base Porphyrinsmentioning
confidence: 83%
“…3b). This similarity between the electrooxidized porphyrin and its protonated product is not specific to the investigated porphyrins [32,33] nor is it specific to the PhCN or CH 2 Cl 2 solvent. The same ''side reaction'' involving conversion of the electrooxidized species to a protonated porphyrin with an unoxidized macrocycle also occurs in CHCl 3 but in this solvent only one major oxidation is observed for 1, 2 and 6.…”
Section: Protonation Of the Phosphorylated Free-base Porphyrinsmentioning
confidence: 83%
“…The bond lengths for 16 p-electron [50,56,58] and 18 p-electron [46,[51][52][53] porphyrin rings in comparison with those of the Pt-complex obtained from X-ray analysis are listed in Table 4. From this table, it is found that there is much similarity in the values of bond distances of 18 p-electron rings and the Pt-complex reported here.…”
Section: X-ray Crystal Structure Of [(Tmp)pt(oh) 2 ]á2metachlorobenzomentioning
confidence: 99%
“…In the oxidative environment of the enzyme, porphyrin p-cation radical with 17 p-electron system has been proposed [22,54,55]. Vaid et al and Yamamoto et al have reported anti-aromatic 16 p-electron porphyrins and their Li + and Zn 2+ complexes [56][57][58][59]. All 20 or 16 anti-aromatic porphyrins have similar features, such as (i) alternating C-C bond distances along the 20 carbon periphery of their porphine ring system, (ii) highly saddle or ruffle distortion of the porphine from planarity, (iii) red shift in Soret band for 20 p-elecron system and blue shift for 16 p-electron system to that of normal porphyrin and (iv) strong paratropic shift in NMR for anti-aromatic porphyrins compared to that of diatropic shift normally seen in aromatic porphyrins.…”
Section: Introductionmentioning
confidence: 99%
“…Porphyrins and their derivatives have been extensively investigated during the past decades owing to their important roles in coordination chemistry, biology, optical power limiting, and other practical applications . All of these technological applications are obviously related to the aromaticity of porphyrins and porphyrinoids.…”
Section: Introductionmentioning
confidence: 99%